Implementing Game-Based Learning (GBL) and Ludic Activities as a Teaching Strategy to Increase Young Learners' Exposure to and Use of the English Language (2023)
ABSTRACT: This action research project explores the effectiveness of implementing Game-Based Learning (GBL) and Ludic Activities to increase the English language exposure and usage among a group of second graders from a public institution in Medellin, Colombia. Initially the terms were defined, then the activities were described and finally, the data collected was analyzed. The tools to collect data were interviews, surveys, students work, students’ English diaries and a teacher’s journal. Findings suggest that the use of GBL and Ludic Activities notably increase students’ exposure to and use of the L2 at the same time they turn the classes student-centered. Moreover, these approaches contribute to a significant boost in motivations and students’ development of social skills. However, challenges emerged in the realm of classroom management, highlighting the need for the research and implementation of different strategies to address this issue.